2004
DOI: 10.1007/s00234-004-1284-1
|View full text |Cite
|
Sign up to set email alerts
|

Dural enhancement with primary calvarial lesions

Abstract: The purpose of this study was to relate the pathological and imaging features of dural enhancement and meningeal sign ("dural tail") on contrast-enhanced T1-weighted magnetic resonance (MR) images from patients with primary calvarial lesions as well to assess the accuracy of MR imaging in predicting dural invasion. Thirty-two calvarial tumors studied with contrast-enhanced MR imaging and histopathological examination of the dural specimens were reviewed. Sixteen patients presented dural enhancement, eight with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…2 Because enhancement may represent tumor invasion, dural resection is prudent if it can be achieved with a low risk of significant morbidity.…”
Section: Treatmentmentioning
confidence: 99%
“…2 Because enhancement may represent tumor invasion, dural resection is prudent if it can be achieved with a low risk of significant morbidity.…”
Section: Treatmentmentioning
confidence: 99%
“…Ahmadi et al11 and Eisen et al9 noted linear dural enhancement in 12 and 7 cases, respectively; dural invasion was not noted in any of these cases. Similarly, Arana et al13 noted linear enhancement in 6 cases, with histologic dural invasion being seen in only one case. In the present study, 15 patients were noted to have linear dural enhancement, with 7 of 15 (46.7%) having dural invasion histologically.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of linear dural enhancement is the most common MRI characteristic for sinonasal and skull base neoplasms 9,11–13. Multiple studies have demonstrated that linear dural enhancement is likely reactive in nature and does not reflect true dural invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Preoperative imaging with computed tomography (CT) and/ or magnetic resonance imaging (MRI) may help predict skull base invasion, but may be associated with both false positives and false negatives with respect to occult invasion. [9][10][11][12][13][14][15] The principal aim of this study was to determine the occult rate of dural invasion in patients with tumors extending to and/or eroding the bony skull base but without overt dural invasion. Furthermore, we explored the prognostic implications of bony skull base erosion and of resecting dura in this group of patients.…”
Section: Introductionmentioning
confidence: 99%